CHECKLIST - PAUL TICHER (Data Protection and the Cloud, 2015)
Throughout this publication various recommendations have been made. They are summarised here for convenience. Before embarking on a cloud computing development ensure that your organisation’s information (and especially IT) security framework is sound, and that responsibility for information security is clearly allocated. Ensure that your organisation’s approach to data protection compliance is well thought out, and that responsibility is clearly allocated. Before selecting a cloud provider, consider whether your data needs to be retained in the European Economic Area, and if so, make this a key selection criterion. For all cloud providers under consideration, check the contract (or standard terms